Bubble point pressures of binary methanol/water mixtures in fine‐mesh screens. Issue 2 (19th December 2013) - Hartwig, Jason; Mann, J. Adin
<x xml:space="preserve">Abstract</x> Binary methanol/water mixture bubble point tests involving three samples of fine‐mesh, stainless steel screens as porous liquid acquisition devices are presented in this article. Contact angles are measured as a function of methanol mass fraction using the Sessile Drop technique. Pretest predictions are based on a Langmuir isotherm fit. Predictions and data match for methanol mole fractions greater than 50% when pore diameters are based on pure liquid tests. For all three screens, bubble point is shown to be a maximum at a methanol mole fraction of 50%. Model and data are in disagreement for mole fractions less than 50%, which is attributed to variations between surface and bulk fluid properties. A critical Zisman surface tension value of 23.2 mN/m is estimated, below which contact angles can be assumed to be zero. Solid/vapor and solid/liquid interfacial tensions are also estimated using the equation of state analysis from Neumann and Good. Published 2013 American Institute of Chemical Engineers AIChE J 60: 730–739, 2014